2024 Recommendations on the Optimal Use of Lipid-Lowering Therapy in Established Atherosclerotic Cardiovascular Disease and Following Acute Coronary Syndromes: A Position Paper of the International Lipid Expert Panel (ILEP) - Banach, Maciej; Reiner, Željko; Surma, Stanisław; Bajraktari, Gani; Bielecka-Dabrowa, Agata; Bunc, Matjaz; Bytyçi, Ibadete; Ceska, Richard; Cicero, Arrigo F G; Dudek, Dariusz; Dyrbuś, Krzysztof; Fedacko, Jan; et al. (Drugs, 2024)
Atherosclerotic cardiovascular disease (ASCVD) and consequent acute coronary syndromes (ACS) are substantial contributors to morbidity and mortality across Europe. Fortunately, as much as two thirds of this disease's burden is modifiable, in particular by lipid-lowering therapy (LLT). Current guidelines are based on the sound premise that, with respect to low-density lipoprotein cholesterol (LDL-C), "lower is better for longer", and recent data have strongly emphasised the need for also "the earlier the better". In addition to statins, which have been available for several decades, ezetimibe, bempedoic acid (also as fixed dose combinations), and modulators of proprotein convertase subtilisin/kexin type 9 (PCSK9 inhibitors and inclisiran) are additionally very effective approaches to LLT, especially for those at very high and extremely high cardiovascular risk. In real life, however, clinical practice goals are still not met in a substantial proportion of patients (even in 70%). However, with the options we have available, we should render lipid disorders a rare disease. In April 2021, the International Lipid Expert Panel (ILEP) published its first position paper on the optimal use of LLT in post-ACS patients, which complemented the existing guidelines on the management of lipids in patients following ACS, which defined a group of "extremely high-risk" individuals and outlined scenarios where upfront combination therapy should be considered to improve access and adherence to LLT and, consequently, the therapy's effectiveness. These updated recommendations build on the previous work, considering developments in the evidential underpinning of combination LLT, ongoing education on the role of lipid disorder therapy, and changes in the availability of lipid-lowering drugs. Our aim is to provide a guide to address this unmet clinical need, to provide clear practical advice, whilst acknowledging the need for patient-centred care, and accounting for often large differences in the availability of LLTs between countries.
Keywords: anticholesteremika; statiny; ateroskleróza; Acute Coronary Syndrome; lidé; Atherosclerosis; akutní koronární syndrom; Anticholesteremic Agents; přehledová literatura jako téma; Hydroxymethylglutaryl-CoA Reductase Inhibitors; LDL-cholesterol; Hypolipidemic Agents; hypolipidemika; Review Literature as Topic; Cholesterol, LDL; Humans